First Report of Pseudopestalotiopsis theae Causing Leaf Spot on Euonymus japonicus in China - Ma, Wanli (Plant disease, 2022)
Euonymus japonicus Thunb., an evergreen shrub, is popular for landscaping in China. In 2021, leaf spot was observed on E. japonicus (about 150 trees) leaves with 40 to 50% disease incidence in Wanzhou urban forest (30°45'N; 108°27'E) of Chongqing, the infected plants were between 5 and 6 years old. The symptoms started to occur from June to July and approximately 30 to 40% of the leaves exhibited leaf spot symptoms from August to September. Initial symptoms appeared as yellow spots of 1.2 to 4.9 mm in diameter, and then expanded to become large and irregular lesions, having white center surrounded by a brown halo. Under humid conditions, black dots appeared in the central part of the spots. In later stage, split and fall of the tissues occurred from the infected spot. To identify the causal agent, infected tissues from 20 samples (from 5 trees) were cut into small pieces (5 mm2), surface-sterilized for 30 s in 75% ethanol and 3 minutes in 3% sodium hypochlorite, rinsed three times in sterile water, placed onto potato dextrose agar (PDA) amended with streptomycin sulfate (50 μg/ml) and incubated at 25°C in dark conditions. Purified eight fungal colonies were white with undulating margins and light cream on the reverse side, measuring 85 mm diameter after 7 days, dark brown to black conidiomata were irregularly scattered and Conidia were observed in 20 days old colonies. Conidia were spindle-shaped, 4.5 to 6.8 × 15.2 to 23.5 μm (n=50), with 4 diaphragms, the three median cells were light to dark brown and the two end cells were colorless. 1 to 3 accessory filaments (5.2 to 22.5 μm long) protrude from theapical cell while a short stalk (3.5 to 5.5 μm long) was attached to the basal cell, these morphological features suggested that the isolates were most likely Pestalotiopsis. sp. Eight colonies were confirmed to be identical based on morphological characteristics. For molecular identification, DNA was extracted from representative strains (YF-5, YF-13, YF-24). The internal transcribed spacer (ITS) region, β-tubulin (TUB2), the translation elongation factor-1 alpha gene (TEF1), genes were amplified using primers ITS5/ITS4, TUB2F/TUB2R, and EF-526F/EF-1567R, respectively (White et al.1990; Glass & Donaldson 1995; O'Donnell & Cigelnik 1997; Carbone &, Kohn.1999). The sequences were deposited in NCBI GenBank YF-24, [ITS; ON204233: TUB2; ON304156: TEF1; ON400075]: YF-5, [ITS; OP379570: TUB2; OP413495: TEF1; OP413496]: YF-13, [ITS; OP379589: TUB2; OP413494: TEF1; OP413497]. Which revealed a 95% similarity to the Ps. theae NTUCC 18-067 [ITS; MT322086: TUB2; MT321888: TEF1; MT321987] ex-type sequences. Based on morphology and multilocus phylogenetic analysis, representative strains were identified as Pseudopestalotiopsis theae. For Koch's postulates, wiped the leaves of six healthy plants of E. japonicus (two-year-old) grown in pots with sterile water, 10 μL of spore suspension (106 spores/ mL) was brushed on five leaves per plant (three plants in total) with a sterile brush, and the other three plants were treated with sterile water instead of spore suspension as control, the plants were placed in a greenhouse at 28°C and 95±1% relative humidity. Seven days after inoculation, brown lesions appeared, similar to those observed in infected plants. Black dots surrounded by a brown halo reappear on the lesions after 12 days, whereas control plants remained healthy. Ps. theae culture was re-isolated from the infected leaves and identified using morphological characteristics and DNA sequence analysis. To our knowledge, Ps. theae can cause diseases on tea plants and has been found in Japan, Thailand and China, this is the first report of leaf spot infection of E. japonicus caused by Ps. theae in China. This disease is reducing the ornamental value of E. japonicus. Our results will contribute to the prevention and cure of leaf spot disease in E. japonicus